The Mediating Effects of Trust and Satisfaction on E-Commerce Repurchase under Deflationary Economic Conditions - Tirsha Alisa; Anna Amalyah Agus (Jurnal Ilmiah Manajemen Kesatuan, 2025)
In deflationary economic conditions, where price sensitivity rises, understanding repurchase intention in e-commerce is crucial. This study explores how customer experience dimensions influence repurchase intention in Indonesia’s home and living e-commerce sector. Adopting the Stimulus–Organism–Response theory, it examines the roles of hedonic, utilitarian, and social values, mediated by customer trust and satisfaction. Data from 340 upper-middle-class respondents were analyzed using PLS-SEM. The findings reveal that customer satisfaction, rather than trust, primarily drives repurchase intention. Perceived privacy and security significantly enhance satisfaction, while hedonic motivation influences trust but not directly satisfaction. Contrary to expectations, personalization, online reviews, and social pressure showed no significant impact, challenging common digital marketing assumptions. Trust and satisfaction act as key mediators, with satisfaction being the dominant pathway to loyalty. These results highlight the critical role of emotional engagement and security in fostering customer loyalty during economic uncertainty. The study suggests e-commerce platforms prioritize secure, emotionally engaging experiences over functional attributes to retain customers in deflationary contexts, offering valuable insights for digital marketers navigating economic downturns.